2017
DOI: 10.1590/1982-0224-20160176
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of elasmobranch species in southeastern Brazil

Abstract: The feeding ecology of five elasmobranch species was studied on the southern coast of Rio de Janeiro, southwestern Atlantic Ocean. The specimens were caught with a trawl or bottom longline between January 2006 and August 2007. The diets of Psammobatis rutrum and Psammobatis extenta appeared to be basically carcino-benthophagous, with a very small niche width. Rioraja agassizii was basically carcino/ichthyo-benthophagous, also with a narrow niche, including teleost fish and shrimp, but in different proportions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
9
0
2
Order By: Relevance
“…Sharpnose shark life cycles are restricted characteristically to coastal environments. The higher frequency of R. lalandii juveniles observed herein at the end of spring and in summer has been reported previously for southeastern Brazil (Motta et al, 2007;Andrade et al, 2008;Viana et al, 2017), while adults have been reported as being more common from April to July (calendar-wise defined by sampling dates, as autumn/spring) with neonates beginning to appear in June and dominating in August and September (spring/summer), the birth season for this species. A high frequency for R. porosus juveniles was also observed herein in summer, seemingly following the same trend in the reproductive cycle as R. lalandii, as observed in Guaratiba, located near Recreio (Ferreira, 1988).…”
Section: Biometric Sharpnose Shark Datasupporting
confidence: 75%
See 1 more Smart Citation
“…Sharpnose shark life cycles are restricted characteristically to coastal environments. The higher frequency of R. lalandii juveniles observed herein at the end of spring and in summer has been reported previously for southeastern Brazil (Motta et al, 2007;Andrade et al, 2008;Viana et al, 2017), while adults have been reported as being more common from April to July (calendar-wise defined by sampling dates, as autumn/spring) with neonates beginning to appear in June and dominating in August and September (spring/summer), the birth season for this species. A high frequency for R. porosus juveniles was also observed herein in summer, seemingly following the same trend in the reproductive cycle as R. lalandii, as observed in Guaratiba, located near Recreio (Ferreira, 1988).…”
Section: Biometric Sharpnose Shark Datasupporting
confidence: 75%
“…All specimens were caught by gillnets, with meshes ranging between 40 mm and 120 mm (Copacabana, 50 mm; Cabo Frio, 45 and 65 mm; Recreio, 40 mm; and Rio das Ostras, 110 to 120 mm), positioned at mid-water depth or at the bottom. These mesh sizes are used throughout the sampling area and allow for comparisons with no fish mesh-size bias (Silva Junior et al, 2008;da Oliveira et al, 2016;Viana et al, 2017;Loto et al, 2018).…”
Section: Sharpnose Shark Sampling and Processingmentioning
confidence: 99%
“…Traditionally, in almost all published studies the vacuity coefficients are less than 20% of the total stomachs analysed (Navia et al ., 2007; Amariles et al ., 2017; Viana et al ., 2017). In this regard, some species of elasmobranchs have particularly high values of emptiness, for example Zapteryx exasperata (76.6%) (Blanco-Parra et al ., 2012), Mobula japanica (76%) ( M. mobular sensu Last et al ., 2016), M. thurstoni (58.3%) and M. munkiana (40%) (Notarbartolo di Sciara, 1988), where other methods such as SIA and molecular techniques were used to describe the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse contexto, o estudo da alimentação dos peixes é de extrema importância, tanto para aprofundar o conhecimento das características biológicas das espécies, mas também como um instrumento de compreensão das interações das diversas populações da ictiofauna e dos seus níveis tróficos na cadeia alimentar (Bennemann et al 2011, Viana & Vianna 2014, Viana et al 2017. Além disso, é por meio da alimentação que os indivíduos obtêm energia e, portanto, estudar a sua dieta auxilia na compreensão das atividades envolvidas no desenvolvimento, crescimento, reprodução e manutenção do organismo (Oliveira et al 2018).…”
unclassified